Italian Jewish Networks from the Seventeenth to the Twentieth Century
X, 219 p.
Keywords: The volume investigates the interconnections between the Italian Jewish worlds and wider European and Mediterranean circles, situating the Italian Jewish experience within a transregional and transnational context that is mindful of the complex set of networks, relations, and loyalties that characterized Jewish diasporic life from the seventeenth to the twentieth centuries. Preceded by a methodological introduction by the editors, the chapters present specific case studies that address rabbinic connections and ties of communal solidarity in the early modern period, and examine the circulation of Hebrew books and the complex overlap of national and transnational identities after emancipation. For the twentieth century, this volume additionally explores the Italian side of the Wissenschaft des Judentums; the role of international Jewish agencies in the years of Fascist racial persecution; the interactions between Italian Jewry, JDPs and Zionist envoys in the aftermath of Word War II; andthe impact of Zionism in transforming modern Jewish identities.